The impact of preoperative anemia on pancreatic resection outcomes. Issue 5 (May 2022) - Pecorelli, Nicolò; Guarneri, Giovanni; Quattromani, Roberto; Arru, Giaime G.; Gozzini, Lorenzo; Lee, Yong H.; Vallorani, Alessia; Turi, Stefano; Partelli, Stefano; Crippa, Stefano; Falconi, Massimo
Abstract: Background: Preoperative anemia is a risk factor for blood transfusions and delayed postoperative recovery, but few data are available for pancreatic surgery. Aim of the study was to analyze the impact of preoperative anemia on outcomes after pancreatic resection. Methods: Retrospective review of 1107 patients resected at San Raffaele Hospital (2015–2018). Preoperative anemia was defined as hemoglobin lower than 130 g/L for men and 120 g/L for women. Primary outcome was 90-day comprehensive complication index (CCI). Analysis was stratified according to type of surgery; proximal resections (pancreaticoduodenectomy and total pancreatectomy) versus distal pancreatectomy. Results: In 776 proximal resection patients, preoperative anemia was associated with increased CCI (24 ± 25 vs. 19 ± 23, p = 0.018) and perioperative allogenic blood transfusions (n = 124, 46% vs. n = 129, 26%; p < 0.001). Multivariate analysis showed that anemia was associated with a 7% (95%CI 0.02–0.57 p = 0.047) increase in CCI, and was an independent factor associated with perioperative blood transfusion (OR 2.762, 95%CI 1.72–4.49, p < 0.001). In 331 distal pancreatectomies, anemia was not associated to increased morbidity but only to an increased risk of perioperative blood transfusion. Conclusion: Preoperative anemia is an independent risk factor for increased complication severity and blood transfusion in patients undergoing major pancreatic resection.